IMPLEMENTATING EDUCATIONAL CONCEPTS OF ATHIYAH AL ABRASYI AT THE GHIFARI FOUNDATION SLEMAN YOGYAKARTA - Arsila, Yusra; Isnaini, Rohmatun Lukluk; Muhammad, Rozhin Wrya (INTIHA: Islamic Education Journal, 2025)
The type of research used by the authors in this study was qualitative research. This method was used to describe the implementation of educational concepts of Atthiyah Al Abrasyi. The data collection techniques were interviews, observation, and documentation. Means of data reduction, data display, conclusion drawing, and data verification were used by the authors as data analysis. The results of this study were the strategies for strengthening the morals of students at the Ghifari Foundation, namely: (a) carrying out praiseworthy moral habits; (b) holding Dhuha prayers and Dhuhur prayers in the congregation; (c) having fun learning methods; and (d) incorporating religious values into every learning activity. The existence of the educational concepts of Athiyah Al Abrasyi at the Ghifari Foundation is contained in the foundation's vision and mission, which is then implemented into a learning strategy. The Ghifari Foundation implements it in the form of the following strategies: (a) instilling love for the Qur'an in children; (b) setting murottal every morning to greet students when they arrive; (c) memorizing selected hadiths using the movement method; (d) memorizing and applying daily prayers; (e) giving appreciation for each student's progress; (f) training students to be brave; and (g) training students to save.